Gut Microbiota, Leaky Gut, and Autoimmune Diseases - Christovich, Anna; Luo, Xin M. (Frontiers in Immunology, 2022)
With the rising prevalence of autoimmune diseases, the role of the environment, specifically the gut microbiota, in disease development has grown to be a major area of study. Recent advances show a relationship and possible cause and effect between the gut microbiota and the initiation or exacerbation of autoimmune diseases. Furthermore, microbial dysbiosis and leaky gut are frequent phenomena in both human autoimmune diseases and the murine autoimmunity models. This review will focus on literature in recent years concerning the gut microbiota and leaky gut in relation to the autoimmune diseases, including systemic lupus erythematosus, type 1 diabetes, and multiple sclerosis.